Work-Life Balance Management in Nepal’s Hospitality Industry - Pandit, Shishir; Sharma, Aaditya Shankar; Devkota, Jiwan; Shrestha, Jhamka Narayan; Lamichhane, Basu Dev (NPRC Journal of Multidisciplinary Research, 2025)
Background: The hospitality industry in Nepal faces significant work-life balance (WLB) challenges due to its demanding work nature, characterized by long and irregular hours, high stress, and emotional labor. Despite its economic importance, the sector struggles with employee burnout and turnover, necessitating research into effective WLB strategies. Objectives: This study (1) examines the impact of extended working hours on work stress and productivity, (2) contrasts the effectiveness of organizational policies, (3) examines the impact of family responsibilities on job performance, (4) quantifies career opportunities as a retention dimension, and (5) pinpoints targeted interventions for enhancing WLB. Methods: There was a mixed-methods design that collected data from 132 hospitality workers through structured online questionnaires. Descriptive statistics were employed to analyze quantitative data on working hours, policies, and stress levels, while qualitative data analyzed employees’ experiences. Findings: The key findings are 31.8% of employees work 8-10 hours a day, and 63.6% suffer productivity losses as a result of working long hours. While 77.3% of firms offer counseling and 84.1% parental leave, only 62.1% of employees are content with WLB. Surprisingly, 81.1% welcome career prospects despite challenges, and 70.5% endure work stress during off-work hours. Conclusion: The study points to important gaps between existing policies and employee needs, highlighting the importance of better deployed flexible working hours, family-friendly policies, and mental well-being measures to enable WLB and retention. Novelty: The study provides the first comprehensive analysis of WLB challenges in Nepal’s hotel sector, offering context-sensitive responses spanning policy effectiveness and ground realities.